Pengurangan Nilai Emisi Co2eq Saat Pandemi Dari Aktivitas Kendaraan Di Fakultas Teknik Universitas Riau - Miftahul Ulum Mareta; Aryo Sasmita; Elvi Yenie (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
One of the activities that produce CO2eq emissions in campus activities is transportation activities by lecturers, staff, and students. The purpose of this study is to calculate the value of CO2eq emissions resulting from activities at the Faculty of Engineering, University of Riau during the pandemic and during normal conditions, analyze the value of CO2eq emissions resulting from the activities of the Faculty of Engineering, University of Riau during the pandemic and during normal conditions, and provide alternatives to minimize CO2eq emissions resulting from activities at the Faculty of Engineering, University of Riau during normal conditions. Results Total CO2eq emissions from the use of operational vehicle fuel by lecturers, staff, and students during the pandemic were 168,248.58 kgCO2eq/year and under normal conditions 253,135.28 kgCO2eq/year. The chosen alternative to reduce CO2eq emissions is to implement a car free day system once a week in the campus area for students who live 2 km walk to campus supported by shuttle buses and communal parking in front of the campus and propose to students to replace the use of motorized vehicles (cars and motorbikes) by bicycle to campus with a distance of 3 km from their residence. Keywords: CO2eq Emission, FT-UNRI, Pandemic, Subtraction alternative